IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT THROUGH THINK PAIR SHARE TECHNIQUE AT EIGHT GRADE OF MTS. SWASTA AL WASHLIYAH 19 PERCUT - Ulfa Rianda (Faculty of Tarbiyah nad Teacher Training, 2021)
The objective of this research is to identify the types of error in using simple present tense in writing descriptive that made by eight grade students of MTsN 2 Deli Serdang, to identify the cause of students make error in using simple present tense in writing descriptive text at MTsN 2 Deli Sedang. This research is qualitative research. The object of research was the eight grade students of MTsN 2 Deli Serdang. The technique of colleting the data are test and questionnaire. The researcher use the technique of analyzing the data from James and Brown. The total of result from students’errors are 49 errors. Then, the students make error in omission are 21 students’ (42,85%), addition 11 students’ (22,44%), misformation 15 students’ (30,61%), and misordering 2 students’ (4,08%). For result of questionnaire the students’ get cause from context of learning, so to minimize he error outcome in simple present tense, the researcher suggest that the teacher should give the explanation how to write a descriptive text to be a good sentence and also give more examples to the students because more example can make the students understand about writing descriptive text. Keywords: descriptive tex, writing, students, present tense